Rapid migrations and dynamics of citizen response - Sahasranaman,A; Jensen,H (Royal Society Open Science, 2019)
One of the pressing social concerns of our timeis the need for meaningful responses to migrantsand refugees fleeing conflict and environmentalcatastrophe. We develop a computational model tomodel the influx of migrants into a city, varyingthe rates of entry, and find a non-linear inverserelationship between the fraction of resident populationwhose tolerance levels are breached due to migrantentry and the average time to such tolerancebreach. Essentially, beyond a certain rate of migrantentry, there is a rapid rise in the fraction ofresidents whose tolerances are breached, even as theaverage time to breach decreases. We also modelan analytical approximation of the computationalmodel and find qualitative correspondence in theobserved phenomenology, with caveats. The sharpincrease in the fraction of residents with tolerancebreach could potentially underpin the intensity ofresident responses to bursts of migrant entry intotheir cities. Given this non-linear relationship, it isperhaps essential that responses to refugee situationsare multi-country or global efforts so that sharpspikes of refugee migrations are equitably distributedamong nations, potentially enabling all participatingcountries to avoid impacting resident tolerancesbeyond limits that are socially sustainable.